The Strategic Role of Lean– A Discussion - Veiga, Gabriela L.; De Lima, Edson Pinheiro; Angelis, Janinis Jan; Da Costa, Sérgio Eduardo Gouvêa (Brazilian Journal of Operations & Production Management, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->Operations strategy and its development have received a lot of attention in the operations management literature. However, literature related to benefits of improvement programs, such as lean production, is often contradictory to operations strategy principles. There is a large body of work arguing that lean can bring substantial performance improvements, indicating that operations strategy formalization might be unnecessary when certain operational processes improvements are applied. However, some literature emphasize the importance of operations strategy, stating that its formulation leads to superior competitiveness when lean techniques are properly related to competitive dimensions and to decision areas. In this study, a comprehensive literature review has been carried out to reveal insights on both streams of study and it is used to conceive a framework and a research interview protocol based on that. Hence, this study compares experts’ view of the strategic role of lean. Such a comparison is done through a range of interviews. The results support the notion that lean can generate a strong advantage in many competitive dimensions; even so, a formal strategy approach is still necessary to focus lean model implementation.